Ethics of care : critical advances in international perspective - Barnes, Marian; Brannelly, Tula (Policy Press, 2015)
"Over the last 20 years there has been a flourishing of work on feminist care ethics. This collection makes a unique contribution to this body of work. The international contributors demonstrate the significance of care ethics as a transformative way of thinking across diverse geographical, policy and interpersonal contexts. From Tronto's analysis of global responsibilities, to Fudge Schormans' re-imagining of care from the perspective of people with learning disabilities, chapters highlight the necessity of thinking about the ethics of care to achieve justice and well-being within policies and practice. This book will be essential reading for all those seeking such outcomes. The international contributors to this unique collection demonstrate the significance of care ethics as a transformative way of thinking across diverse geographical, policy and interpersonal contexts."--Publisher's description.